Remake, remodel : women's magazines in the digital age - Duffy, Brooke Erin (Book collections on Project MUSE., 2013)
What is a magazine? For decades, women's magazines were regularly published, print-bound guidebooks aimed at neatly defined segments of the female audience. Crisp pages, a well-composed visual aesthetic, an intimate tone, and a distinctive editorial voice were among the hallmarks of women's glossies up through the turn of this century. Yet amidst an era of convergent media technologies, participatory culture, and new demands from advertisers, questions about the identity of women's magazines have been cast up for reflection. This title offers a unique glimpse inside the industry and reveals how executives and content creators are remaking their roles, their audiences, and their products at this critical historic juncture.